Pelatihan Pemasaran Digital UMKM Kerajinan Tas Motif Aceh "Mom n Me" untuk Meningkatkan Kualitas Produk - Hakim Muttaqim; Fauzi; Azka Rizkina (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Micro, Small and Medium Enterprises is one of the strengths of the national economy. During the Covid-19 pandemic, Micro, Small and Medium Enterprises became the most vulnerable sectors to be affected, especially in terms of product marketing and sales. Mom n Me is a Micro, Small and Medium Enterprise in the field of sewing Aceh motif bags. This business has been running for 5 (five) years since 2018, and in 2020 it has been transformed from a patchwork sewing business to expanding to the field of sewing Aceh handicraft bags by raising local wisdom. Mom n Me is also one of the Micro, Small and Medium Enterprises that has felt the impact of the Covid-19 pandemic. The purpose of this service activity is to improve partners' skills in digital-based marketing as well as to improve the quality of partner products. The solution offered in this activity is to provide digital marketing training such as the use of social media to increase product sales and provide training on using the official Mom n Me application/website. This application can help Micro, Small and Medium Enterprises to carry out promotions and sell products without having to have large spaces such as shops and storefronts. The method used in this activity consists of forming an activity team, conducting analysis, implementing activities, and evaluating. The results of the service activities are the official Mom n Me application/website as a tool for online marketing and sales as well as providing training to business owners, so they can operate the application/website.